Preparation, Physicochemical Evaluation and Characterization of Mucoadhesive Buccal Gels Impregnated with Benzydamine Hydrochloride for the Effective Treatment of Aphthous Stomatitis: Effect of Different Grades of HPMC Polymer on In vitro and Ex vivo Performance - Sharma, Deepak; Sharma, Amit; Garg, Rajeev (Drug Delivery Letters, 2019)
Background: Drug delivery across the buccal mucosal epithelium membrane is one of the promising routes to treat various recurrent ailments of the oral cavity. Aphthous stomatitis is an inflammatory oro-mucosal disorder associated with mucous membranes of mouth, cheek, lips, tongue or gingival region. Benzydamine Hydrochloride was designated as a drug of choice by virtue of its anesthetic, antimicrobial, analgesic, anti-inflammatory and antibacterial action. The medication administration through the buccal route is very testing because of restricted absorption area, shorter residence time and movements of the target region. Objective: To prepare mucoadhesive buccal gel of Benzydamine Hydrochloride and assess the effects of various HPMC polymer on in vitro and ex vivo performance with the assumption to extend the residence period and achieve maximum drug release in a sustained manner at the target region. Methods: Mucoadhesive buccal gels were formulated by utilizing various HPMC grades that served as rate controlling and mucoadhesive polymer. A total of 24 preparations were formulated and subjected to physicochemical evaluation and characterization. Results: It was found that the physicochemical parameters varied according to the polymer type and concentration used. Eight formulations were exposed to ex vivo study by virtue of maximum in vitro permeation and mucoadhesion properties. Because of higher ex vivo drug permeation and mucoadhesion, F24 was considered as the final optimized formulation. FTIR and DSC established compatibility between the drug and excipient. The amorphous nature of the drug within the optimized formulation was further unveiled by XRD study. Conclusion: The developed buccal gel has a great prospective in contrast to marketed conventional preparation for treating aphthous stomatitis.
Keywords: aphthous stomatitis